Reverse Logistics Management for End-of-Life Vehicles (ELVs) - Khlaikhaek, Saringkhan; Ngammeesri, Laksamee; Ngoenchan, Janejira (Ph.D. in Social Sciences Journal, 2023)
This academic article aims to analyze approaches to reverse logistics management for end-of-life vehicles, and idle, it is passenger vehicles with a tendency to end-of-life. By analysis of Sustainable Development guidelines, regulations, or laws in electric vehicles technology, energy, reverse logistics, and financial returns and environment. Findings are as follows: (1) Regulatory and laws measures effectively manage end-of- life vehicles. Therefore, Thailand should push the regulations and laws in accordance with the guidelines. The European Union’s “Directive 2000/53/EC” (2) The government plays an important role in supporting the implementation of the reverse logistics network throughout the supply chain. with modern technology to separate parts that reduce the impact on society and the environment is sustainable development and (3) Network reverse logistics management for end-of-life It is a comprehensive operation and comprehensive implementation of regulatory and laws measures including collection, sorting, inspection, resale, re-use, repair, refurbishment, remanufacturing, recycling, recovery, and disposal that can generate financial returns, and reduce the impact on the environment. This is the most efficient recovery of resources.